(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In fact, the education of young people, which is the foundation of our future, is formed first of all in the family. Character traits characteristic of a person, as well as ethnic characteristics characteristic of our nation, feelings such as respect for elders, respect for children, love for the Motherland, and duty are all formed in the family. Deviant behavior among children, such as crime, drug addiction, aggression, and suicide, which are foreign to our society, are caused by improper organization of interpersonal relationships in the family. In our young families, communication between children, teenagers, adults and other persons is not satisfactory, it is currently carried out through communication with mass media, as well as the concept of "we" and the attitude towards it are not sufficiently developed.